HIGH SCHOOL STUDENTS’ EMOTIONAL EXPERIENCES OF ONLINE LEARNING DURING COVID-19 PANDEMIC PERIOD (Practitioner Research, 2022)
Purpose - This research aims to explore the emotional experiences of online learning among high school students during the pandemic period. Underlying issues that led to the development of the emotions, coping mechanisms, and support received were also looked into in the study.Methodology - This qualitative study employed a case study method, involving semi-structured interviews. By using Purposive Sampling, 12 high-school students were selected and interviewed on topics related to i) their emotional experiences in online learning; ii) the strategies they used to deal with their emotions, and iii) the type of support thatthey received throughout their online learning experiences. Thematic Analysis and In-vivo Coding were used to interpret the data and generate suitable themes and sub-themes for the study.Findings - Findings show that students experienced a variety of emotions of unhappiness, happiness, discomfort, frustration, anger,stress, annoyance, exhaustion, shyness, and the feeling of being distracted during the time of online learning during the Covid-19pandemic. Data also show that students coped with their emotions through interaction with others, taking a breather, keeping tothemselves, managing the interruptions, and also maintaining focus. When it came to the support received, family support, peer support, financial support, and educational support were the sub-themes that emerged.Significance - The results of this study contribute to the understanding of high school students’ feelings towards online learning and see how they are coping with it during the Covid-19 pandemic.